Formulasi Lip Balm Alami Ekstrak Minyak Esensial Jeruk Nipis (Citrus aurantifolia L.) Sebagai Pencerah Bibir - Usviany, Veny; Azizah, Indah Nur (Asosiasi Guru dan Dosen Seluruh Indonesia, 2022)
Lips are one part of the face whose appearance affects the aesthetic perception of the face which requires external protection to maintain its beauty However, the continuous use of synthetic lip balms will cause damage to the skin of the lips which becomes dry, cracked, and dull color is getting worse.. This study aims to formulate lip balm preparations containing lime essential oil and test its effectiveness. This research was conducted experimentally, using a qualitative research type with a descriptive method. The results showed that lime essential oil can be formulated as a lip balm preparation with the following ingredients: (1) Lime essential oil extract, (2) Coconut oil, (3) Cera alba, (4) Nipagin, (5) Glycerin, (6) BHT, (7) Cocoa butter, all homogeneous preparations, stable during 28 days of storage, have semi-solid dosage forms such as lip crayons and have a distinctive citrus aroma, pH value of 5-7 is safe and comfortable when applied to the lips, easy preparation smeared and effective to use. From the test results on volunteers, it can be concluded that lip balm preparations with a concentration of lime essential oil 16.5% showed effectiveness as lip lightening faster than lip balm preparations with concentrations of 5% and 8.5%.